UPACARA NGABEN DI KREMATORIUM SANTHAYANA DENPASAR - Budiasa, Kadek (Pangkaja: Jurnal Agama Hindu, 2024)
The modernization of the Ngaben Ceremony at the Santhayana Crematorium in Denpasar was carried out due to a conflict which resulted in structural sanctions for Pakraman Village so that it could oppress minority groups. In practice desa pakraman in Bali, this minority group is those who get the fewest votes compared to other groups. From this point of view, the position and role of village leaders will have a special position because they can strengthen the position of the majority. This article descriptively narrates the form, function and Implications of the Modernization of the Ngaben Ceremony at the Denpasar Santhayana Crematorium. The essence of the crematorium cremation ceremony is the same as the conventional cremation ceremony, namely the process of returning all the elements in the human body to their origins in the universe, namely melting the human body called Panca Maha Bhuta Alit into Panca Maha Bhuta Agung through burning. The existence of the Santhayana Crematorium has the functions of Socio-Religious, Cultural Preservation, Transition to Modernization of Balinese Hindu Culture, Functions of Economic Management and Practical Religion. While the Implementation of the Modernization of the Ngaben Ceremony at the Denpasar Santhayana Crematorium has implications for Social Engineering, Community Economic Implications, Cultural Tourism, Tradition Implications, and Community Empowerment Implications.